Transient Reactor Test Facility Advanced Transient Shapes. (3rd October 2019) - Holschuh, Thomas; Woolstenhulme, Nicolas; Baker, Benjamin; Bess, John; Davis, Cliff; Parry, James
Abstract: The Transient Reactor Test (TREAT) facility restarted transient operations in 2018 and has met or exceeded expectations for reactor experiments. TREAT's flexibility in power shaping provides the ability to prescribe a variety of operating conditions for test specimens, including shaped transients, steady-state irradiations, natural pulses, and clipped pulses, to deliver the necessary energy deposition and energy deposition rate. The initial operations following the TREAT restart were designed to mimic historical operations to confirm TREAT's capability. Then, studies were performed to evaluate the minimum pulse width possible in the facility as well as reactor power profiles characteristic of a loss-of-coolant accident (LOCA); both were achieved with excellent results. This paper highlights the following: 1. The TREAT facility has been restarted to resume nuclear fuel safety research. 2. Initial reactor operations have mimicked historical operations. 3. A minimum pulse width has been achieved by control rod reinsertion during pulse. 4. Power profiles characteristic of a LOCA accident were performed.